Where to Begin? Pressing Issues Organization of Educational Process - Aleksandr Vasilievich Kirillov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The contradiction existing now between the growing requirements to quality of vocational training and retraining of public servants and opportunities of the higher school presses the permission. Modern educational process at the higher school is in a strip of prompt changes. Introduction of information and communicative technologies in the Russian universities and institutes, and, in particular, in system of educational institutions of the Russian academy of national economy and public service, raised a question not only of readiness of material base, but also of ability and opportunities of the faculty and students (listeners) to perceive new approaches. Improvement of a control system of independent work on the basis of broad application of new information and communicative technologies by means of which it is possible to raise professional standard of public servants considerably can become one of ways of permission of this contradiction. For the solution of this task in article a number of questions is considered: what organizational and pedagogical and didactic conditions of application of new information technologies of training (including technologies of distance learning) in independent work of students and listeners, what possibilities of their effective use at independent studying of historical disciplines, what pedagogical technologies it is necessary to be the basis for intellectually developing computer test tasks and interactive computer textbooks on disciplines “National history” and “History of public administration in Russia”? Effective use of potential of individual-based and logiko-information approaches in pedagogics of the higher school, as shown in article, it is necessary to consider as the “catalyst” capable to initiate dynamic development of sociocultural processes in education of public servants.